2022
DOI: 10.1039/d2tc04186c
|View full text |Cite
|
Sign up to set email alerts
|

Strong electron–phonon coupling driven charge density wave states in stoichiometric 1T-VS2 crystals

Abstract: A charge density wave (CDW) transition is one of the fundamental quantum phenomena used to unveil the interactions between electrons and phonons that are coexisting or competing with other intriguing...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…We note finally that in a similar fashion, V 5 Se 8 was previously procured from seed layers of VSe 2 during thin film growth or by increasing the substrate temperature during growth or annealing of single-layer VSe 2 . , In a similar vein, the chemical vapor deposition growth of VS 2 nanosheets generally leads to the simultaneous presence of VS 2 and V 5 S 8 . , In each case, the small differences in formation energy between the self-intercalated material and the TMDC are emphasized. Here, we showed that providing extra V atoms after an initial growth step can help to favor one phase over the other and enables one to grow phase-pure ultrathin V 5 S 8 -derived materials down to the minimal thickness of 1.15 nm.…”
Section: Resultsmentioning
confidence: 99%
“…We note finally that in a similar fashion, V 5 Se 8 was previously procured from seed layers of VSe 2 during thin film growth or by increasing the substrate temperature during growth or annealing of single-layer VSe 2 . , In a similar vein, the chemical vapor deposition growth of VS 2 nanosheets generally leads to the simultaneous presence of VS 2 and V 5 S 8 . , In each case, the small differences in formation energy between the self-intercalated material and the TMDC are emphasized. Here, we showed that providing extra V atoms after an initial growth step can help to favor one phase over the other and enables one to grow phase-pure ultrathin V 5 S 8 -derived materials down to the minimal thickness of 1.15 nm.…”
Section: Resultsmentioning
confidence: 99%